Analisis Pembentukan Portofolio Optimal Dengan Menggunakan Model Indeks Tunggal DalamMengambil Keputusan Investasi Pada Saham LQ45 Yang Terdaftar Di BEI Periode 2019-2021 - Bambang Suhada; Febriyanto; Bella Selviana Putri (Universitas Muhammadiyah Metro, 2024)
Investment is the main key in achieving increased economic growth, which is reflected in the ability to increase growth rates and income levels. The greater the investment of a country, the greater the level of economic growth that can be achieved. In this study the authors chose LQ45 companies as research objects. The LQ45 stock index was chosen because it is a stock that is quite attractive to investors. This is because LQ45 shares have high liquidity and market capitalization value. But at this time the LQ45 stock index is experiencing an unstable decline seen since 2019 of 3.2%, 2020 of -7.8%, 2021 -2.5% (IDX, 2021). This research was conducted using a quantitative descriptive research method that aims to find out which stocks are included in the optimal portfolio candidate. to find out how big the proportion of each share. And also to know the return and risk that will be accepted. The population used in this study is 45 shares of LQ45 companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample selection in this study used a purposive sampling technique, namely a sampling technique with certain considerations or criteria Sugiyono (2010). With the criteria, namely companies that are active and consistently listed on the LQ45 Index during the 2019-2021 period, a total of 34 company shares. Based on the analysis that has been carried out by calculating using the formula in Microsoft Excel, the results in this study are from 34 samples of LQ45 company shares, there are 4 company shares that are candidates in the optimal portfolio, namely Aneka Tambang (Persero) Tbk. (ANTM), Erajaya Swasembada Tbk. (ERAA), Vale Indonesia Tbk. (INCO), and XL Axiata Tbk. (EXCL). Of the 4 companies, the proportion of shares selected was ANTM, the highest with 0.3669 (36.7%), then INCO with 0.2556 (25.6%), ERAA with 0.2182 (21.8%), and EXCL of 0.1593 (15.9%). Of the stocks that make up the optimal portfolio, it has a return of 0.0333 (3.33%) and a risk of 0.0459 (4.59%).